PENGARUH KARAKTERISTIK PEKERJAAN TERHADAP MOTIVASI INTRINSIK UNTUK BERBAGI PENGETAHUAN SECARA ONLINE DENGAN MENGGUNAKAN AFFECTIVE COMMITMENT SEBAGAI MEDIASI PADA KARYAWAN PT. PERTAMINA (PERSERO) ACEH - Rahmad Rizki, Mahdani Ibrahim (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2018)
This study aims to determine the effect of Job Characteristics on Intrinsic Motivation to share knowledge online by using Affective Commitment as mediation. Sample used in this research is employees of PT. Pertamina (Persero) Aceh. This research method used questionnaire as research instrument. Questionnaires were distributed as many as 97 questionnaires. Sampling technique using probability sampling. Hierarchical Linear Modeling (HLM) is used as an analytical method to determine the effect of the variables involved. The result of the research shows that (1) Job Characteristics has a significant effect on Intrinsic Motivation to share knowledge online, (2) Affective Commitment has significant influence on Intrinsic Motivation to share knowledge online, (3) Job Characteristic have significant influence to Affective Commitment, (4) Job Characteristics have a significant effect on Intrinsic Motivation to share knowledge online with Affective Commitment as mediation.Keywords: Job Characteristics, Intrinsic Motivation, Affective Commitment